Salt tolerance evaluation and key salt-tolerant traits at germination stage of upland cotton - An, Mengjie; Huang, Xinhui; Long, Yilei; Wang, Yin; Tan, Yanping; Qin, Zhen; Ai, Xiantao; Wang, Yan (Frontiers in Plant Science, 2025)
Cotton is an important cash crop with a certain salt tolerance, but its germination stage is very susceptible to the damage of salt stress, causing significant yield loss. However, few studies have evaluated the cotton salt tolerance and selected salt tolerance traits at germination stage. Therefore, in this study, 16 cotton samples with geographical representation were randomly selected from 308 cotton germplasms to determine the optimal 200 mmol·L-1 NaCl in cotton germination experiments. On this basis, the salt tolerance of 308 upland cotton varieties and the growth, ion distribution and transport of highly salt-tolerant and non salt-tolerant cotton germplasms were analyzed. The results showed that the 308 germplasms were classified into five classes through cluster analysis, i.e, (1) highly salt-tolerant germplasms (HST, 49), (2) salt-tolerant germplasms (ST, 169), (3) moderately salt-tolerant class (MST,43), (4) lowly salt-tolerant germplasms (LST, 16), and (5) non-salt-tolerant germplasms (NST, 31). By calculating the salt tolerance index (STI) of various cotton germination and growth parameters and principal component analysis, combined with the correlation analysis and linear regression between mean membership function value (MFV) and STI, the key indexes of cotton germination and growth under salt stress, including total fresh weight, shoot fresh weight, and shoot length, were determined. In addition, three salt tolerance evaluation models constructed with different variables (6 variables in Model 1; 3 variables in Model 2; 1 variable in Model 3) found that the total fresh weight was the most reliable trait for the salt tolerance evaluation. In practical application, the variable selection for modelling could be adjusted based on the experimental workload. The comparison of the K+, Na+, and Ca2+ contents between HST and NST found that the higher the salt tolerance of cotton germplasms, the lower the Na+ content in the root system. Besides, the ion ratios and ion selective transport coefficients (ST) was found to be significantly positively correlated with the salt tolerance of cotton. This study will provide a basis for evaluating and breeding salt-tolerant cotton germplasms.